A Missional perspective of John 4:1-42 : Hearing Jesus and the Samaritan woman and its Implicationsfor the Mission of the Contemporary Church - Kok, Jacobus (Kobus) (University of Pretoria, 2014)
Dissertation (MA Theol)--University of Pretoria, 2014.